ANALISIS PENGARUH RETURN ON ASSET (ROA), RETURN ON EQUITY (ROE), NET PROFIT MARGIN (NPM), DAN DEBT TO RETURN (DER) TERHADAP HARGA SAHAM SYARIAH DI BURSA EFEK INDONESIA - Sabrina, Iputa Leyha; Fauzan, Fauzan (LP2M Universitas Bina Bangsa, 2025)
This study aims to obtain empirical evidence and analyze the influence of Return on Asset (ROA), Return on Equity (ROE), Net Profit Margin (NPM), Debt to Return (DER) on sharia stock prices on the Indonesian stock exchange for the 2019-2022 period. The sample in this study is companies listed in the Jakarta Islamic Index during the period 2019 to 2022. According to certain criteria, as many as 112 samples over the last four years. The analysis used in this study is multiple linear regression. The results showed that ROA, ROE, DER had an effect on stocks while NPM had no effect on stock prices